ANALISIS PENGARUH EARNING, CASH FLOW, NILAI BUKU, DAN NILAI PASAR TERHADAP PERGERAKAN STOCK RETURN PADA SAHAM LQ-45 DI BURSA EFEK JAKARTA - Muhammad Zilal Hamzah (Media Riset Akuntansi, Auditing & Informasi, 2007)
The objective of this study is to know the relationships and significant effect between earning, cash flow, book value and market value toward stock return. The samples for this study consist of 26 companies that consistently exist in LQ-45 in Jakarta Stock Exchange.A multiple linear regressions is used to determine whether independent variable effect significantly. This study shows that earning and cash flow positive and significantly affect stock return. Book value is positive and insignificant affect stock return. Meanwhile, market value is significantly but negative relation with stock return. This study also find the low earning growth and high earning growth of firms affect to stock return. The finding of this study also suggest that more external various factors can be consider in influence stock return.Keywords: earning, cash 'low, book value, market value, stock return.